2020
DOI: 10.18196/ijief.2123
|View full text |Cite
|
Sign up to set email alerts
|

Muzakki Potentials’ Role in Alleviating Poverty (Study Case in Aceh)

Abstract: Zakat is an obligation in Islam which commands followers to donate a small amount of money to the poor, the needy and other particular recipients determined by the Qur'an. Since zakat is obligatory only for the rich, the system should be able to reduce inequality and poverty. Aceh has implemented a zakat management program since 2006; however, its impact has not been evident. This study aims to analyze the impact of potential muzakki on poverty reduction in Aceh and to identify the main factors contributing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(11 reference statements)
0
4
0
1
Order By: Relevance
“…This approach is more stable where the value remains in the standard of living so that comparisons can be made with other regions or other countries. Meanwhile, the relative approach is determined/determined subjectively by the economic conditions of the local community and is local in nature so that it cannot be compared between regions (Pratama and Rahadiana, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This approach is more stable where the value remains in the standard of living so that comparisons can be made with other regions or other countries. Meanwhile, the relative approach is determined/determined subjectively by the economic conditions of the local community and is local in nature so that it cannot be compared between regions (Pratama and Rahadiana, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A study on the effect of Zakat in Aceh showed that even though 60 percent of Zakat's recipients are the poor and the needy, it did not reduce poverty significantly. (Pratama & Rahadiana, 2020). Other recent studies about Zakat reinforced the notion since they revealed the insignificance of Zakat in reducing poverty (R. R. Aziz, 2018;Nurjanah et al, 2019;Tawakkal & Sapha, 2018).…”
Section: Introduction 11 Backgroundmentioning
confidence: 93%
“…The study built two models to examine the impact of the collection of Zakat on the zakat distribution and the impact of the distribution on poverty reduction. As for the model specification, we use the study from Pratama & Rahadiana (2020) as a reference since they used natural logarithm transformation in their model. The natural logarithm transformation is necessary to preserve the linear model when there is a non-linear relationship (Benoit, 2011).…”
Section: Model Developmentmentioning
confidence: 99%
“…BMT terdiri atas dua istilah, yakni baitul maal dan baitul tamwil. Baitul maal berkontribusi pada pengumpulan dan penyaluran dana untuk kepentingan sosial (Isbah, 2019), antara lain zakat (Pratama & Rahadiana, 2020), infaq (Priyono, 2017), dan shodaqoh (Mardiyah & Ryandono, 2016). Sedangkan baitul tamwil berkontribusi pada bisnis yang bertujuan untuk memperoleh keuntungan (laba).…”
Section: Iunclassified